2010
DOI: 10.2355/isijinternational.50.1380
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective Optimization of Ironmaking in the Blast Furnace with Top Gas Recycling

Abstract: Concern about the growing carbon dioxide content in the atmosphere has induced increasing research activities in the search for means to suppress the emissions of CO 2 in primary steelmaking. Blast furnace top gas recycling, combined with CO 2 stripping, has been proposed as a promising concept. The paper presents a numerical analysis of top gas recycling under massive oxygen enrichment of the blast based on a simulation of the process chain from coal and ore to liquid steel. Because of the conflicting goals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…A third kind of framework is been used by Saxen et al [29], Helle et al [30], and Wikulund et al [31,32] in the assessment of the economic potential of biomass utilization in a steel plant. Originally this method has been used for the analysis of the economic prospects of technological innovations in steelmaking (see Pettersson and Saxen) [33].…”
Section: Economical Constrains Of Bio-pcimentioning
confidence: 99%
“…A third kind of framework is been used by Saxen et al [29], Helle et al [30], and Wikulund et al [31,32] in the assessment of the economic potential of biomass utilization in a steel plant. Originally this method has been used for the analysis of the economic prospects of technological innovations in steelmaking (see Pettersson and Saxen) [33].…”
Section: Economical Constrains Of Bio-pcimentioning
confidence: 99%
“…[13] Moreover, multi-objective optimization has been conducted to minimize the production costs and CO 2 emission. [14] Recently, carbon flow analysis was used to investigate the effects of lowcarbon technologies on the carbon emissions of the iron and steel manufacturing system. [15,16] The mass and energy balance models for BF require some parametric hypothesis such as stack efficiency, direct reduction ratio, and top gas efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Refs. [36,37], Mitra et al [38] omitted the simplifying linearization step and conducted an optimization of the two objectives (CO 2 emission minimization and costs minimization) for a steel plant by using genetic algorithms, the results showed that the blast furnace could be operated from moderately oxygen enriched blast to full oxygen enriched blast with preheated CO 2 -stripped recycled top gas. Then, the top gas recycling with CO 2 -stripped gas injection was studied with an optimization model of a steel plant [39].…”
Section: Introductionmentioning
confidence: 98%
“…Wang et al [34,35] conducted CO 2 emissions optimizations of a system of blast furnace/basic oxygen furnace by mixed integer linear programming method, and found that increasing the coke consumption and the silicon content in the hot metal can decrease the CO 2 emission and energy consumption. Helle et al [36,37] established an optimization model of a blast furnace process under high oxygen enrichment with top gas recycling by using linear programming method, and obtained the optimal states of the CO 2 emissions minimization objective, costs minimization objective [36] and the multi-objective considering low CO 2 emission and low costs [37]. Based on Refs.…”
Section: Introductionmentioning
confidence: 99%